Konstitusionalitas Open Legal Policy mengenai Kebijakan Earmarking Pajak Karbon di Indonesia - Pertiwi, Mahaarum Kusuma; Wisaksono, Praditya Janu (Jurnal Hukum & Pembangunan, 2024)
The Law on Harmonization of Tax Regulation mandates government regulation to regulate the allocation of carbon tax revenue for controlling climate change. Based on Article 13 paragraph (12) and paragraph (15) letter b of the Law on Harmonization of Tax Regulation as well as the Constitutional Court's judicial review decisions regarding open legal policies and tax earmarking, this article answers questions regarding the legal construction of open legal policy options in Indonesia which confirms further delegation of carbon tax earmarking through government regulation. The government may allocate state revenue from carbon tax to control climate change. This means that carbon tax earmarking is not absolute. If the government chooses to carry out carbon tax earmarking, then the regulation must be in accordance with or based on government regulations which are first submitted to the House of Representatives for discussion or agreement during the preparation of the Draft of the State Revenue and Expenditure Budget. In substance, the government regulation in question is only permitted to detail provisions that have been regulated by the Law on Harmonization of Tax Regulation and the law regarding the State Revenue and Expenditure Budget as a result of the agreement between the government and the House of Representatives regarding carbon tax earmarking. Apart from that, this government regulation must also pay attention to the provisions in the Environmental Protection and Management Law, the Law Ratifying the Paris Agreement to the United Nations Framework Convention on Climate Change, Government Regulations on the environment, and Government Regulation concerning Procedures for Implementing Tax Rights and Fulfilling Tax Obligations.